Barques are generated in posterior hippocampus and phase reverse over lateral posterior hippocampal surface. (April 2022) - Kokkinos, Vasileios; Urban, Alexandra; Frauscher, Birgit; Simon, Mirela; Hussein, Helweh; Bush, Alan; Williams, Ziv; Bagić, Anto I.; Mark Richardson, R.
Highlights: Barques are predominantly localized in the posterior part of the human hippocampus. No independent barques were found to occur exclusively in the anterior hippocampus. The posterio-lateral hippocampal barque phase reversal can explain the positive polarity of scalp 14&6/sec spikes. Abstract: Objective: To investigate whether barques can be localized across the hippocampal longitudinal axis with sufficient specificity. Methods: We identified 51 focal epilepsy patients implanted with a minimum of two electrodes – unilateral anterior and posterior - in either hippocampus. We used visual inspection of the intracranial electroencephalogram (iEEG) and 3D brain volume spectrum-based statistical parametric mapping (SPM) to localize barques. Results: In 18/51 patients (35.29%), barques were identified in 22/70 (31.42%) hippocampi. In all hippocampi (100%), barques were present in the posterior hippocampus, while 9 (40.90%) showed concurrent non-independent barque activity anteriorly (P < 0.0001). Statistical parametric mapping confirmed the posterior barque localization, with significant differences in t-values (t(27) = 8.08, P < 0.0001) and z-scores (t(24) = 6.85, P < 0.0001) between anterior and posterior hippocampal barque activity. Posterior lateral extrahippocampal contacts demonstrated phase reversals of positive polarity during barque activity (P = 0.0092, compared to anterior extrahippocampal contacts). Conclusions: This study highlights the posterior hippocampal predominance of barques. Our findings are concordant with the posterior distribution of the scalp manifestation of barques as "14&6/sec positive spikes". The posterio-lateral hippocampal barque phase reversal can explain the positive polarity of scalp 14&6/sec spikes. Significance: Understanding the properties of barques is critical for the iEEG interpretation in epilepsy surgery evaluations that include the hippocampus.